Pretreatment with metformin reduced dendritic spine loss following cardiac ischaemia/reperfusion injury by preventing amyloid beta aggregation, brain inflammation and mitochondrial dysfunction. (25th November 2020) - Chattipakorn, S.C; Leech, T; Apaijai, N; Higgins, L; Jinawong, K; Palee, S; Maneechote, C; Jaiwongkam, T; Chattipakorn, N
Abstract: Background: Cognitive impairment is a major complication following acute myocardial infarction (AMI). Although reperfusion therapy is a standard treatment for AMI, it leads to additional damage to the heart, known as cardiac ischaemia/reperfusion (I/R) injury. In addition to cardiac damage, brain damage was observed following cardiac I/R including brain mitochondrial dysfunction, brain inflammation, amyloid beta aggregation, resulting in dendritic spine loss. Metformin has been reported as an effective neuroprotective agent in several brain pathologies such as stroke, diabetes-related cognitive decline, and cerebral I/R injury. However, the effects of metformin on the brain pathology after cardiac I/R have not been investigated. Purpose: We hypothesized that metformin attenuates brain damages and increases dendritic spine density by preventing brain mitochondrial dysfunction, brain inflammation, and amyloid beta aggregation in non-diabetic rats. Methods: Male Wistar rats (n=30) were received either sham operation (n=6) or cardiac I/R operation (n=24). Cardiac I/R was done by left anterior descending coronary artery ligation for 30 min followed by a reperfusion for 120 min. In cardiac I/R group, rats were randomly divided into 4 interventions (n=6/group) as follows; 1) vehicle (a normal saline solution), 2) 100 mg/kg of metformin (Met 100), 3) 200 mg/kg of metformin (Met 200), and 4) 400 mg/kg of metformin (Met 400). Sham operated rats were received normal saline solution. Metformin or vehicle was given to the rats at 15 min prior to cardiac ischemia via intravenous injection. At the end of reperfusion, rats were sacrificed, and the brain was rapidly removed to determine brain mitochondrial function, microglial morphology, Alzheimer's related protein, and dendritic spine density. Results: Cardiac I/R led to brain mitochondrial dysfunction as indicated by increasing reactive oxygen species (ROS) levels, mitochondrial membrane depolarization, and mitochondrial swelling, compared with sham. Moreover, microglial hyperactivity was observed, together with tau hyperphosphorylation and amyloid beta aggregation, compared with sham (Fig. 1). All dosages of metformin successfully activated AMPK at the similar levels, compared with vehicle group. Mitochondrial ROS and membrane potential changes were equally improved in all groups of metformin, compared with vehicle. Although mitochondrial swelling was reduced in all groups of metformin, it was markedly reduced in Met 400 group (Fig. 1). Furthermore, microglial hyperactivity, amyloid beta aggregation, and tau hyperphosphorylation were equally reduced in all groups of metformin. For dendritic spine density, metformin significantly increased dendritic spine density, and the density was highest in Met400 group, compared with other groups (Fig. 1). Conclusion: Pretreatment with metformin offers neuroprotection against the brain damages following cardiac I/R injury in a dose-dependent manner. Funding Acknowledgement: Type of funding source: Public grant(s) – National budget only. Main funding source(s): Thailand Research Fund (SCC), and National Science and Technology Development Agency Thailand (NC)